PENERAPAN PEMBELAJARAN REACT TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Ihsani, Annisa Zahra; Langitasari, Indah; Affifah, Isriyanti (Jurnal Inovasi Pendidikan Kimia, 2020)
Critical thinking skills (CTS) are needed in chemistry learning, especially on solubility and the solubility product constant concept because this concept has contextual, complex characteristics and most of the concepts are obtained through practical activities. The learning that can train students CTS is REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning. This study aims to determine of application REACT learning to students CTS on solubility and the solubility product constant concept. The design of this study was one group pretest posttest with purposive sampling technique. The instrument was valid and reliable 12 essay questions and observation sheets. Data analysis technique was done by analysis descriptive using N-Gain and statistical analysis using paired sample t-test. The result showed that the N-Gain value with the medium category on 6 indicator CTS. These results were supported with the result of the paired sample test are acquired the significance value <0,05 and effect size results with high criteria that indicated REACT learning has a positive effect on students CTS on solubility and the solubility product constant concept